VALUASI EKONOMI SUMBERDAYA HUTAN MANGROVE DI DESA PALAES KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Benu Olfie L. Suzana; Jean Timban; Rine Kaunang; Fandi Ahmad (Sam Ratulangi University, 2011)
The purpose of this study to determine the economics value of mangrove forest ecosystems, as well asits contribution to society in the region of mangrove research sites in the Palaes Village, District of WestLikupang, North Minahasa regency. In this research, using primary and secondary data. The variablesmeasured were the direct benefit of the value generated from direct utilization of mangrove forests such asthe potential for wood (timber and firewood), palm leaves craftsmen , catching fish, shrimp and crab(Rp/year). The value of benefits Indirect value resulting from the utilization of mangrove forest indirectlynamed as breaking waves (break water) (Rp/year). Value of benefit options, namely the economic valuederived from potential direct or indirect utilization of a resource / ecosystem in the future the value ofBiodiversity (Rp/year).Based on INP calculation to determine the existence of a species in a community under study, obtainedPalaes Village mangrove forest dominated by Rhizophora at 109,499. INP data from other speciesin a row on the kind of Brugiera of 58,088, amounting to 57,492 Ceriops species, Xilocarpus of 41,491,20,860 species of Sonneratia and Avicennia species amounted to 12,860.Based on the calculations found that the benefits obtained if mangrove forests are maintained atRp10,888,218,123,/year, calculated from the sum of the direct benefits other than timber potential, indirectbenefits and benefits options. Meanwhile, if the potential for exploitation of timber obtained a profit ofRp273,617,273/year. It can be concluded that if the mangrove forest is maintained, then the benefits will39.8 times greater than exploiting the natural resources of mangrove forests Palaes Village.By considering the total economic value derived from the mangrove forest ecosystem in Palaes Village,it has the benefits of mangrove forest and an important functions as economic resources and ecologicalresources for the life of the people who are around him. Therefore, the presence of (physical condition)of mangrove forest ecosystems must be maintained as an asset development, be it by local communitiesand other parties such as government, private sector, researchers and LSM, so that development activitiescan work well and the availability of mangrove forest resources remain secure.